The Prevalence and Associated Factors of Protein Energy Malnutrition among under Five Year Children in Pediatric OPDs of Public Health Institution in Yirgalem Town, Southern Ethiopia, 2017 - Tegegne, Kaleab Tesfaye; Berisha, Iyasu Estiphanos (International Journal of Child Health and Nutrition, 2019)
Introduction: Protein energy malnutrition is one of the leading causes of morbidity and mortality in children under the age of five in developing countries. Ethiopia being one of these countries malnutrition is an important public health problem and among the highest in the world Objectives: The main objective of this study is to assess the prevalence and associated factors of protein energy malnutrition among under-five children in pediatric OPDs of public health institutions at Yirgalem town, Dale woreda, Sidama zone, SNNPR, Ethiopia from September 18-26, 2017. Methodology: Institutional based cross sectional study was conducted in pediatric OPDs of public health institutions in Yirgalem town, on a total of 204 children age less than five years from September 18-26, 2017. Study subjects were selected by using quota sampling technique. Interviewer administered structured questionnaire and anthropometric measurements were used to collect data. Data was analysed using SPSS version 20.0statistical software. Result: This study indicated that the prevalence of stunting wasting and Under-weight was 41.2%, 1.7% and 25% respectively. Factors showed statistically significant association in multivariate analysis were family planning use by mother, children eat together with older siblings and exclusive breast feeding with P-value (0.02), (0.036) and (0.002) respectively. Conclusion: This study reviled that the prevalence of stunting, wasting and under-weight were higher among under-five children participated in this study. Thus children are at a higher risk of under nutrition related morbidity and mortality. Further progress in under nutrition prevention can be achieved by specifically targeting children at their early age and conducting tailored public education to improve the nutritional status of the study subjects.